Kajian Literatur Terhadap Peran Transfer Pengetahuan Dalam Konteks Perusahaan Multinasional - Jondry Adrin Hetharie; Abraham Rieuwpassa (Journal of Business Application, 2022)
The purpose of this study is to demonstrate and summarize the important aspects of knowledge transfer in the context of multinational corporations. Design/methodology /approach; the review of aspects of SD is based on 15 journals published from 2005 to 2015 academic database, namely Emerald, by looking at the keywords "knowledge transfer" and "Multinational Corporation". Findings; through a literature review, this paper recommends To increase the competitive advantages of a global company, HR activities need to focus on developing its international capabilities. Companies that have successfully globalized their HR activities describe 5 important characteristics found in the literature review. Research limitations/implications; only used 15 journals as study sources. Originality/value; this study presents a literature review on important aspects of multinational companies, namely: knowledge transfer.